2021
DOI: 10.3390/agriculture11080783
|View full text |Cite
|
Sign up to set email alerts
|

Can Trust Motivate Farmers to Purchase Natural Disaster Insurance? Evidence from Earthquake-Stricken Areas of Sichuan, China

Abstract: Natural disasters cause great losses of property and life in many areas of China. However, rural residents do not always insure themselves against these losses. Measuring the correlation between trust and farmers’ behavior related to the purchasing of natural disaster insurance is of great significance to the implementation of natural disaster insurance pilot programs and insurance systems in China. This article analyzes data from a survey of 327 households in four districts and counties of Sichuan Province, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In natural capital, compared with using past savings, the exchange of property for cash ( p = 0.000, B = −2.199) is significantly negatively correlated with the distance between the house and the river and lake, which is consistent with the research conclusion of Baker [ 49 ]. The closer the distance to the river, the greater the loss and damage caused by the flood, and selling the property can quickly solve the economic needs.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In natural capital, compared with using past savings, the exchange of property for cash ( p = 0.000, B = −2.199) is significantly negatively correlated with the distance between the house and the river and lake, which is consistent with the research conclusion of Baker [ 49 ]. The closer the distance to the river, the greater the loss and damage caused by the flood, and selling the property can quickly solve the economic needs.…”
Section: Resultssupporting
confidence: 86%
“…Based on the analysis of the occurrence time of perennial floods and the prediction results of floods, the farmers in flood-prone areas will change the types of crops into waterlogging-resistant crops to keep their crops able to withstand the impact of floods, or choose to advance or postpone the planting date of crops to avoid the invasion of floods, and ensure the family’s economic benefits by changing crops. Because of the perennial nature and great destructiveness of floods, families suffering from disasters choose to buy some natural disaster accident insurance and rely on insurance premiums to make up for the losses caused by floods [ 49 ]. This is a livelihood strategy choice of scientific disaster prevention.…”
Section: Methodsmentioning
confidence: 99%
“…Young farmers or farmers with higher incomes are more likely to buy disaster insurance due to previous disaster experiences, feelings about disasters, or where they reside (Bao et al, 2021). A study indicated how younger farmers experiencing financial hardship and residing in remote areas are more likely to experience drought-related stress (Austin et al, 2018).…”
Section: Agementioning
confidence: 99%
“…For regional heterogeneity analysis, the study used the topographic data of the village where the sample households resided (Type) and the ages of the household heads as control variables (Age). Based on previous research studies and the actual situation of the study areas, we also chose family characteristic factors (education of household head (Edu), the number of laborers in a household (Labor), whether family members are village cadres (Vcadres), forest resource factors (timber forest area (Timber_A), economic forest area (Economic_A), bamboo forest area (Bamboo_A), and forest fragmentation (Areatract)), economic and geographical factors (village population (V_pop), per capita net income in the village (V_income), and the distance from village to nearby town (Distance)) (Bao et al, 2021;Lian et al, 2021;Wang et al, 2021;Liu et al, 2022).…”
Section: Control Variablesmentioning
confidence: 99%